Safety and effectiveness of the INVATEC MO.MA® proximal cerebral protection device during carotid artery stenting: Results from the ARMOUR pivotal trial - Ansel, Gary M.; Hopkins, L. Nelson; Jaff, Michael R.; Rubino, Paolo; Bacharach, J. Michael; Scheinert, Dierk; Myla, Subbarao; Das, Tony; Cremonesi, Alberto (Catheterization and cardiovascular interventions, 2010)
Objective: The multicenter ARMOUR (ProximAl PRotection with the MO.MA Device DUring CaRotid Stenting) trial evaluated the 30‐day safety and effectiveness of the MO.MA® Proximal Cerebral Protection Device (Invatec, Roncadelle, Italy) utilized to treat high surgical risk patients undergoing carotid artery stenting (CAS). Background: Distal embolic protection devices (EPD) have been traditionally utilized during CAS. The MO.MA device acts as a balloon occlusion “endovascular clamping” system to achieve cerebral protection prior to crossing the carotid stenosis. Methods: This prospective registry enrolled 262 subjects, 37 roll‐in and 225 pivotal subjects evaluated with intention to treat (ITT) from September 2007 to February 2009. Subjects underwent CAS using the MO.MA device. The primary endpoint, myocardial infarction, stroke, or death through 30 days (30‐day major adverse cardiac and cerebrovascular events [MACCE]) was compared to a performance goal of 13% derived from trials utilizing distal EPD. Results: For the ITT population, the mean age was 74.7 years with 66.7% of the cohort being male. Symptomatic patients comprised 15.1% and 28.9% were octogenarians. Device success was 98.2% and procedural success was 93.2%. The 30‐day MACCE rate was 2.7% [95% CI (1.0–5.8%)] with a 30‐day major stroke rate of 0.9%. No symptomatic patient suffered a stroke during this trial. Conclusions: The ARMOUR trial demonstrated that the MO.MA® Proximal Cerebral Protection Device is safe and effective for high surgical risk patients undergoing CAS. The absence of stroke in symptomatic patients is the lowest rate reported in any independently adjudicated prospective multicenter registry trial to date. © 2010 Wiley‐Liss, Inc.